Prevalence and predictors of return visits to pediatric emergency departments. Issue 12 (23rd October 2014) - Akenroye, Ayobami T.; Thurm, Cary W.; Neuman, Mark I.; Alpern, Elizabeth R.; Srivastava, Geetanjali; Spencer, Sandra P.; Simon, Harold K.; Tejedor‐Sojo, Javier; Gosdin, Craig H.; Brennan, Elizabeth; Gottlieb, Laura M.; Gay, James C.; et al.
<x xml:space="preserve">Abstract</x> OBJECTIVE To determine the rate of return visits to pediatric emergency departments (EDs) and identify patient‐ and visit‐level factors associated with return visits and hospitalization upon return. DESIGN AND SETTING Retrospective cohort study of visits to 23 pediatric EDs in 2012 using data from the Pediatric Health Information System. PARTICIPANTS Patients <18 years old discharged following an ED visit. MEASURES The primary outcomes were the rate of return visits within 72 hours of discharge from the ED and of return visits within 72 hours resulting in hospitalization. Results: 1, 415, 721 of the 1, 610, 201 ED visits to study hospitals resulted in discharge. Of the discharges, 47, 294 patients (3.3%) had a return visit. Of these revisits, 9295 (19.7%) resulted in hospitalization. In multivariate analyses, the odds of having a revisit were higher for patients with a chronic condition (odds ratio [OR]: 1.91, 95% confidence interval [CI]: 1.86‐1.96), higher severity scores (OR: 1.42, 95% CI: 1.40‐1.45), and age <1 year (OR: 1.32, 95% CI: 1.22‐1.42). The odds of hospitalization on return were higher for patients with higher severity (OR: 3.42, 95% CI: 3.23‐3.62), chronic conditions (OR: 2.92, 95% CI: 2.75‐3.10), age <1 year (1.7–2.5 times the odds of other age groups), overnight arrival (OR: 1.84, 95% CI: 1.71‐1.97), and private insurance (OR: 1.47, 95% CI: 1.39‐1.56). Sickle cell disease and cancer patients had the highest rates of return at 10.7% and 7.3%, respectively. CONCLUSIONS Multiple patient‐ and visit‐level factors are associated with revisits. These factors may provide insight in how to optimize care and decrease avoidable ED utilization. Journal of Hospital Medicine 2014;9:779–787. © 2014 Society of Hospital Medicine